Industrial Homework, Economic Restructuring and the Meaning of Work - Leach, Belinda (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1998)
Abstract The recent "renaissance" of industrial homework is attributed to the search for flexible labour in processes of economic restructuring. This paper argues that common-sense ideas about the meaning of work in western capitalist society underpin the use of industrial homework as a flexible strategy for economic efficiency in the context of corporate and state restructuring of the economy. Drawing on an ethnographic study of homework in Southern Ontario, the paper discusses some of the ways in which the meaning of work is ambiguous, situationally specific and continuously redefined in the homework context. It is argued that this is possible because of the awkward location of the homework labour process, occupying as it does space and time usually associated with home and family.